(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
The article highlights the importance of digital management in the placement of crops, the application of a crop rotation system and the efficient use of water resources in agriculture. The role of the “CropAgro” information system in automating agrotechnical processes, ensuring environmental sustainability and increasing yields will be analyzed on a scientific basis. It will be shown that the use of the system will lead to an increase in production efficiency and a reduction in land degradation